1997
DOI: 10.1097/00007890-199704150-00013
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tacrolimus (Fk506) and Cyclosporine for Immunosuppression After Cadaveric Renal Transplantation1

Abstract: Tacrolimus is more effective than cyclosporine in preventing acute rejection in cadaveric renal allograft recipients, and significantly reduces the use of antilymphocyte antibody preparations. Tacrolimus was associated with a higher incidence of neurologic events, which were rarely treatment limiting, and with posttransplant diabetes mellitus, which was reversible in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
530
9
16

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,067 publications
(581 citation statements)
references
References 13 publications
26
530
9
16
Order By: Relevance
“…The relatively lower reversibility in the American Phase III Multicenter Trial is probably related to a protocol-driven minimum dose of prednisone in that trial. 4,5 Given the improved immunosuppressive efficacy associated with tacrolimus, 1-6 the transiently increased incidence of PTDM may well be considered clinically acceptable. Certainly, the potential for PTDM has not prevented the successful use of tacrolimus in kidney/pancreas transplantation, where a number of reports have described its efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relatively lower reversibility in the American Phase III Multicenter Trial is probably related to a protocol-driven minimum dose of prednisone in that trial. 4,5 Given the improved immunosuppressive efficacy associated with tacrolimus, 1-6 the transiently increased incidence of PTDM may well be considered clinically acceptable. Certainly, the potential for PTDM has not prevented the successful use of tacrolimus in kidney/pancreas transplantation, where a number of reports have described its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…and the final incidence ranged from 1.4% to 12.6%, with a reversibility of 37% to 83%. 1,4,5,[12][13][14][15] Subgroup analysis was performed in only one study, the American Phase III Multicenter Trial. It showed a higher incidence of PTDM in African American than in Caucasian recipients, and an association in all patients with higher tacrolimus levels and steroid doses.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] The use of this agent in the pediatric population is less well described. We and others have previously reported that its use in pediatric patients is associated with excellent patient and graft survival results in a relatively small number of patients.…”
mentioning
confidence: 99%